A Case Report Chronic Recurrent Traumatic Tongue Ulcer: Modern Treatment Approaches - Ghoshal, Dr. Nanda Kishore (Medical Science Journal for Advance Research, 2021)
Ulcerations are characterized by defects in the epithelium, underlying connective tissue, or both. Due to diversity of causative factors and presenting features, diagnosis of oral ulcerative lesions might be quite challenging. Tongue ulcers are open sores or cuts on the tongue. Tongue ulcers can be painful and raw and can be irritated by eating and drinking. One of the most common types of tongue ulcers is the canker sore, which may arise for an unknown reason or be linked to a number of different irritants. This article is an attempt to elaborate the treatment protocols with couple of case reports